COMPUTER-AIDED ENGINEERING: Seven-League Boots to the Gates of Progress. - Williams, John michael (ETC: A Review of General Semantics)
Discusses the significance of abstraction to the development of integrated electronic circuits. Disadvantages of using breadboarding in testing circuit designs; Use of the Logician workstation from Daisy Systems in facilitating circuit designs; Impact of computer-aided engineering on the design of logic circuits.